Digitalisation in agriculture: a scoping review of technologies in practice, challenges, and opportunities for smallholder farmers in Sub-Saharan Africa - Choruma, Dennis Junior; Dirwai, Tinashe Lindel; Mutenje, Munyaradzi; Mustafa, M.; Chimonyo, V. G. P.; Jacobs-Mata, Inga; Mabhaudhi, T. (Elsevier, 2024)
Digitalisation in agriculture is transforming the way farming is practised worldwide, and its potential benefits for smallholder farmers in sub-Saharan Africa (SSA) are particularly promising. Yet, scientific evidence on the digital technologies utilised by smallholder food producers in SSA and the associated challenges still needs improvement. This review attempts to provide a thorough overview of the technologies currently being employed by smallholder farmers in SSA while also exploring the associated challenges and opportunities. Through a systematic literature search, 27 relevant studies were analysed to identify the region-wise current technologies, challenges, and opportunities. Results show that various digital technologies are employed, including digital extension services and digital marketing of agricultural products. These technologies improve access to information and markets and enhance productivity. However, challenges hinder widespread adoption. Limited internet connectivity, low digital literacy, inadequate infrastructure, and affordability issues impede progress. Gender disparities further limit the equitable distribution of digitalisation benefits. Despite these challenges, significant opportunities arise from adopting digital technologies. The potential advantages are market access, better decision-making capabilities, and increased income and livelihoods. Digitalisation offers transformative possibilities for smallholder farmers in SSA. Overcoming barriers such as limited connectivity and low digital literacy is crucial. By harnessing the opportunities digital technologies can offer, the livelihoods of smallholder farmers can be uplifted, contributing to the growth of agriculture in SSA.